Efforts for ex-situ conservation of Maleo (Macrocephalon maleo) birds through egg hatching - Rusiyantono Yohan; Tanari Mobius; Mumu Mohamad Ilyas (BIO Web of Conferences)
The Maleo bird (Macrocephalon maleo) is a native to Sulawesi Island of Indonesia, where there is currently a downward trend in numbers owing to habitat loss, predation, and poaching of their eggs. A viable option for overcoming the population decline is conserving the species, as controlling its egg hatching. This research examined the methodological aspects, challenges, and outcomes of the Maleo birds’ egg at hatching programs and the importance of storing in situ conservation efforts. The results showed Maleo eggs can hatch at incubator temperature conditions of 32 – 36°C, and the highest hatchability was obtained at 34°C.